Information processing in info-communication media of geodynamic monitoring on the basis of adaptive queuing system - Kuzichkin O. R.; Eremenko V. T.; Loginov I. V.; Grecheneva A. V.; Eremenko A. V.; Dorofeev N. V. (Bulletin of Electrical Engineering and Informatics, 2020)
The paper considers the problem of modeling the processing of geodynamic information in a reconfigurable information-communication environment of geodynamic monitoring based on an adaptive queuing system. It was established that due to the complexity and diversity of geodynamic information, the number of geodynamic control points is expanding and the number of controlled parameters, the number of controlled objects of natural-technical systems (NTS) are increasing. This leads to an increase in the overall load on the info-communication monitoring environment, an increase in the processing time and the response time of the NTS geodynamic stability control system to negative changes. This leads to the need for adaptive optimization of the info-communication environment of geodynamic monitoring. The model of a composite stream describing the change in the nature of the tasks performed by geodynamic monitoring was determined, approaches to reconfiguration management based on minimization of the loss functional were proposed. The constructed model of the process of functioning and the analytical dependencies obtained for it allow analyzing the process of processing geodynamic information in info-communication environments to optimize the mechanisms of their functioning.